DIGITAL ASSERTIVENESS: A STUDY OF ASSERTIVE SPEECH ACTS IN SYDNEY SERENA’S VLOGS - Lakantu, Meidistiani; Yuliati (Universitas Negeri Semarang, 2025)
This study investigated the representation of assertive speech acts in the vlogs of Sydney Serena, a popular Gen-Z content creator. Given the growing significance of digital communication and its pedagogical value in EFL contexts, the research focuses on how assertive utterances are linguistically and functionally expressed in informal, unscripted digital content. The study aimed to (1) identify the types of assertive speech acts used in Sydney Serena‘s vlogs, (2) explore their communicative functions across various contexts, and (3) examine the linguistic structures that reflect the speaker's degree of certainty and stance. Using a qualitative content analysis approach, 200 utterances were purposively sampled from two selected vlogs. The analysis was grounded in Searle‘s (1979) taxonomy of speech acts and Kreidler‘s (1998) communicative focus framework. The findings revealed that stating and reporting were the most frequent types of assertive acts, while functions such as informing, confessing, suggesting, and narrating were commonly observed. Linguistic analysis showed that declarative sentences, modal verbs, and reporting verbs were strategically used to convey varying degrees of certainty and speaker stance. The study concluded that assertive speech acts in vlogs enhance personal expression and serve as valuable models for authentic and confident language use, offering practical implications for English language learners and educators.